PHILIPPINE FOREIGN POLICY ADDRESSING THE SOUTH CHINA SEA DISPUTE: A RATIONAL MODEL ANALYSIS - Fikriya Husna Inayah; Yanyan Mochamad Yani; Darmansjah Djumala (Jurnal Dinamika Global, 2025)
This study analyzes the Philippines' foreign policy in the South China Sea dispute during the Ferdinand Marcos Jr. era using the Rational Model. The results show a significant transformation of the Rodrigo Duterte era to a concordance strategy with the United States during the Marcos Jr. era. The failure of Duterte's pro-China approach, which actually increased the aggressiveness of the Chinese Coast Guard and did not provide the expected concessions, became a policy lesson for the Marcos Jr. administration. The concordance strategy was shown through the expansion of the Enhanced Defense Cooperation Agreement, the intensification of military exercises, the modernization of military capabilities, the institutionalization of intelligence sharing, and active participation in multilateral forums. This qualitative research, with data triangulation, reveals that the Philippines' chosen strategy reflects a rational calculation that aligning with the United States provides greater benefits for securing maritime sovereignty and regional stability than confronting China.